Household-head members and their participation in the San Pedro Credit Cooperative Inc. - Tambanillo, Loyalda L (1990.)
Credit Cooperatives are designed for the low income sector of the community. The San Pedro Credit Cooperative, Incorporated in San Jose, Antique is existing for almost 25 years. Its long duration of operation could be accounted for by the participation of the people in the organization. Thus, the study was made. The objectives of the study were met:, 1) The household-heads are mostly between 36-51 years old, farmers, they belong to the low income group, acquisition of higher education for them is of considerable importance and most of them are ordinary members. 1) The household-heads are participative in the activities of the organization, they do deposit money and they do attend meetings of the organization. They are active members of the organization. 3) As to payment behavior, majority of them do pay regularly their loans in the organization. A few of them were declared delinquents but many of them were not. To sum up, the members of the cooperative, are generally cooperative as such. That maybe the reason why the organization has existed for so long a time.
Thesis (Undergraduate, Bachelor of Arts in Community Development) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: San Pedro Credit Cooperative